Systematic Literature Review: Filsafat dalam Aksiologi Ilmu - Manullang, Santi Meilan (Journal of Innovation in Teaching and Instructional Media, 2025)
This research aims to systematically examine literature related to philosophy in the axiology of science, namely the branch of philosophy that discusses the value, benefits and impact of science on human life and society. Using the Systematic Literature Review (SLR) method, this study identifies, analyzes and synthesizes scientific articles, books and other relevant academic sources. The focus of the study includes: (1) the relationship between the axiology of science and ethics and morality, (2) the social and cultural implications of the application of science, and (3) the role of axiology in determining the responsibilities of scientists. The research results show that the axiology of science is a critical framework in guiding the responsible use of science for the benefit of humanity. In addition, the importance of axiological reflection in scientific practice helps prevent potentially harmful misuse of science. This research contributes to the development of a more holistic philosophical perspective regarding science as part of meaningful human life.